2012
DOI: 10.1186/1744-8069-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Peripheral Kappa Opioid Receptors Inhibits Inflammatory Hyperalgesia via Activation of the PI3Kγ/AKT/nNOS/NO Signaling Pathway

Abstract: BackgroundIn addition to their central effects, opioids cause peripheral analgesia. There is evidence showing that peripheral activation of kappa opioid receptors (KORs) inhibits inflammatory pain. Moreover, peripheral μ-opioid receptor (MOR) activation are able to direct block PGE2-induced ongoing hyperalgesia However, this effect was not tested for KOR selective activation. In the present study, the effect of the peripheral activation of KORs on PGE2-induced ongoing hyperalgesia was investigated. The mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 40 publications
1
34
1
3
Order By: Relevance
“…antagonism of the γ-isoform resulted in a more profound and prolonged anti-allodynic effect. These data conflict with those of Ferreira and colleagues [13; 14] who found that morphine’s peripheral anti-hyperalgesia actions are dependent on intact PI3Kγ in the paw. This discrepancy might, in part, be attributed to many differences in protocols, because the two studies used different antagonists with different relative γ/α selectivities, however, Ferreira’s group observed a similar loss of morphine efficacy following the use of PI3Kγ antisense, which strengthens their observation.…”
Section: Discussioncontrasting
confidence: 91%
“…antagonism of the γ-isoform resulted in a more profound and prolonged anti-allodynic effect. These data conflict with those of Ferreira and colleagues [13; 14] who found that morphine’s peripheral anti-hyperalgesia actions are dependent on intact PI3Kγ in the paw. This discrepancy might, in part, be attributed to many differences in protocols, because the two studies used different antagonists with different relative γ/α selectivities, however, Ferreira’s group observed a similar loss of morphine efficacy following the use of PI3Kγ antisense, which strengthens their observation.…”
Section: Discussioncontrasting
confidence: 91%
“…Furthermore, Xu et al [10] found that inhibition of PKB/Akt activation in the spinal cord decreased abnormal pain behaviors, suggesting that PKB/Akt signal pathway activation might contribute to the development of neuropathic pain. However, the results from Ferreira's laboratory showed that blockade of PI3K/Akt pathway prevented opioids-induced antinociception [7,8]. Similarly, we revealed that intrathecal dexmedetomidine upregulated spinal pAkt expression and alleviated mechanical allodynia in CCI rats, suggesting that PKB/Akt signaling activation might mediate dexmedetomidine-induced antiallodynia.…”
mentioning
confidence: 57%
“…Recently, it has been found that stimulation of the PI3K/Akt signaling pathway by opioid receptors directly blocked inflammatory hyperalgesia [7,8]. Moreover, a previous report showed that dexmedetomidine likely activated PKB/Akt signaling via a 2 adrenoceptors to reduce cell death and to provide renoprotection, suggesting a link between a 2 adrenoceptors and PKB/Akt pathway [9].…”
mentioning
confidence: 97%
“…Some studies demonstrated that inflammatory cytokines (such as TNF-α, IL-6, and iNOS) and inducible enzymes such as COX-2 are both induced through the NF-κB pathway [30,31]. Excess amount of NO plays an important role in the aggravation of inflammatory diseases; thus, NO production and iNOS expression are considered pharmacologic targets for antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%